Inverse association between body mass index and all-cause mortality in rural chinese adults: 15-year follow-up of the Anqing cohort study - Yun Song; Jie Yang; Yue Zhang; Xiao Huang; Xiping Xu; Lishun Liu; Binyan Wang; Ziyi Zhou; Zhuo Wang; Xianhui Qin; Genfu Tang; Jingyi Li; et al. (BMJ Open)
Objective To investigate the association between body mass index (BMI) and all-cause mortality in a Chinese rural population.Design Prospective cohort study.Setting This study was conducted from 2003 to 2018 in Anqing, Anhui Province, China.Participants 17 851 participants aged 25–64 years (49.4% female) attending physical examinations and questionnaire were included in this study. The inclusion criterion was families having a minimum of three participating siblings. The exclusion criteria included participants without family number and BMI data at baseline.Outcome measures The outcome measure was all-cause mortality. Generalized estimating equation (GEE) regression analysis was performed to determine the association between baseline BMI and all-cause mortality.Results During a mean follow-up period of 14.1 years, 730 deaths (8.0%) occurred among men, and 321 deaths (3.6%) occurred among women. The mean BMI for males was 21.3±2.5 kg/m2, and for female it was 22.1±3.1 kg/m2. Baseline BMI was significantly inversely associated with all-cause mortality risk for per SD increase (OR, 0.79 (95% CI, 0.72 to 0.87) for males; OR, 0.88 (95% CI, 0.76 to 1.01) for females). When BMI was stratified with cut points at 20 and 24 kg/m2, compared with the low BMI group, a significantly lower risk of death was found in the high BMI group (BMI ≥24: OR, 0.57 (95% CI, 0.43 to 0.77) in males; 0.65 (95% CI, 0.46 to 0.93) in females) after adjustment for relevant factors.Conclusions In this relatively lean rural Chinese population, the risk of all-cause mortality decreased with increasing BMI. The excess risk of all-cause mortality associated with a high BMI was not seen among this rural population.